Revision of the New World species of the genus Pelecorhynchus Macquart, 1850 (Diptera: Pelecorhynchidae) - Llanos, Lorena; Gonzalez, Christian R.; Saldarriaga-Córdoba, Mónica (Zootaxa, 2015)
The New World species of the genus Pelecorhynchus Macquart, all of which are only known from Chile, are revised. Two new species are described, Pelecorhynchus hualqui sp. nov. and Pelecorhynchus toltensis sp. nov. All nine New World species in the genus are redescribed and illustrated, and a key to the species is provided.